Belize : 2009 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Belize. (IMF Staff Country Reports; Country Report, 2009)
Belize's economy is projected to decelerate in 2009 owing to the global downturn. Real GDP growth is projected at 1 percent, reflecting the impact of declining tourism, remittances, and foreign direct investment inflows. Executive Directors have welcomed the broadly favorable economic performance in 2008, and have commended the authorities' commitment to pursue sound macroeconomic and financial sector policies to manage near-term risks. Directors have also emphasized that strong macroeconomic policies are necessary to underpin this exchange rate regime and help raise international reserves to a comfortable level.